Developing Academic Institution: Narrative Inquiry on Proposing English Department - Hari Prastyo (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
Innovation in academic environment is the urgent thing that university must be done in this era. There are many innovative strategies that can be done in academic environment. One of the strategies is proposing new department that community needs in global era. This article will discuss about innovative strategy in proposing English Department based on local wisdom and strength of university. It is kind of research article that uses Narrative Inquiry. The researcher writes narratively and academicly the strategy in proposing English Department. He tries to do need analysis by using observation and unstructered interview. Based on the observation and unstructered interview, the researcher creates academic Draft, then he presented the academic draft at International Conference on Linguistics, ELT, and Literature (ICOLEL). At last, he revised the academic draft for proposing English Department as Final Draft academically. This research article be useful for institution that will develop instittuion academically. This kind of article can be used as a model for academician in creating innovative way at academic environment.